Fermentation processes engineering in the food industry - Soccol, Carlos Ricardo; Pandey, Ashok; Larroche, Christian (Boca Raton, Fla. : CRC Press/Taylor & Francis Group, LLC, 2013)
With the advent of modern tools of molecular biology and genetic engineering and new skills in metabolic engineering and synthetic biology, fermentation technology for industrial applications has developed enormously in recent years. Reflecting these advances, Fermentation Processes Engineering in the Food Industry explores the state of the art of the engineering technology aspects of fermentation processes in diverse food sectors. The book describes the benefits of fermented foods in human health in both dairy and non-dairy products and beverages. It examines applications of microalgae in the food industry and explains the application of metabolic engineering in the production of fermented food ingredients. Exploring a host of important topics in engineering fermentation processes, the book covers topics such as: Methods and techniques for the isolation, improvement, and preservation of the microbial cultures used in the food fermentation industry; The fundamentals of fermentation processes, modes of fermentation, and the principles of upstream operation; Physical and chemicals factors that affect fermentation processes; Different types of fermenters employed in submerged and solid-state fermentation; Unitary operations for solid-liquid separation, concentration, and drying of fermented foods; Instrumentation and control of industrial fermentation processes. The final chapter discusses the potential application of a biorefinery concept to add value to food industry wastes and presents a case study describing an integrated project in which the concept was applied. An essential reference for all food sector professionals, this volume surveys critical trends in the food, beverage, and additive industry and explores the sustainability of these processes.
1. Applications of metabolic engineering in the production of fermented foods and food ingredients / Dimitris Charalampopoulos and Colin Webb -- 2. Isolation, improvement and preservation of microbial cultures / Syed G. Dastager -- 3. Physical and chemical factors affecting fermentation in food processing / Antonella Amore and Vincenza Faraco -- 4. Upstream operations of fermentation processes / Parameswaran Binod, Raveendran Sindhu and Ashok Pandey -- 5. Theoretical tools to predict physiochemical properties of industrial foods and cultivation media / AndrLebert -- 6. Characterization of bioreactors using computational fluid dynamics / Christophe Vial and Youssef Stiriba -- 7. Laboratory and industrial bioreactors for submerged fermentations / Parvinder Kaur, Ashima Vohra and Tulasi Satyanarayana -- 8. Laboratory and industrial bioreactors for solid-state fermentation / JosAngel Rodruez-Le, Daniel Ernesto Rodruez-Ferndez and Carlos Ricardo Soccol -- 9. Downstream operations of fermented products / Jio Car de Carvalho, Adriane Bianchi Pedroni Medeiros, Daniel Ernesto Rodruez-Ferndez, Luiz Alberto, J{u2D6E}ior Letti, Luciana Porto de Souza Vandenberghe, Adenise Lorenci Woiciechowski and Carlos Ricardo Soccol -- 10. Instrumentation and control of industrial fermentative processes / Alexandre Francisco de Moraes Filho, Alysson Hikaru Shirai, Wilerson Sturm and Dario Eduardo Amaral Dergint -- 11. Fermented foods and human health benefits of fermented functional foods / Juliano De Dea Lindner, Ana L{u2D63}ia Barretto Penna, Ivo Mottin Demiate, Caroline Tiemi Yamaguishi, Maria Rosa Machado Prado and JosLuis Parada -- 12. Industrial fermentation for production of alcoholic beverages / Saurabh Jyoti Sarma, Mausam Verma and Satinder Kaur Brar -- 13. Production of dairy products / Luciana Porto de Souza Vandenberghe, Caroline Tiemi Yamaguishi, Cristine Rodrigues, Maria Rosa Machado Prado, Michele Rigon Spier, Adrianne Bianchi Pedroni Medeiros and Jio Car de Carvalho -- 14. Dairy and nondairy probiotic products and beverages / Jean-Luc Tholozan and Jean-Luc Cayol -- 15. Bioadditives produced by fermentation / Juliano Lemos Bicas, Mio Roberto Marostica, Junior, Francisco F{u2862}io Cavalcante Barros, Gustavo Molina and Gl{u2875}cia Maria Pastore -- 16. Microalgae for food production / Jorge Alberto Vieira Costa and Michele Greque de Morais -- 17. Biorefinery concept applied to valorization of Agro-food coproducts and wastes: integrated process for waste recycling and effluent treatment / Carlos Ricardo Soccol, Susan Grace Karp, Paula Fernandes de Siqueira, Csia Tiemi Nemoto Sanada, Vanete Thomas-Soccol and Ashok Pandey.
Includes bibliographical references and index.
Keywords: Fermented foods; Food industry and trade; Fermentation